Manhood crisis in chuck palahniuk's Fight Club and Choke - Vafa, Amirhossein (2010)
The following thesis explicates how in Chuck Palahniuk’s Fight Club (1996) and Choke (2001), the anonymous narrator and Victor Mancini struggle with a certain crisis of manhood as a result of the “contradictory experiences of power” under the impositions of hegemonic masculinity in addition to a sense of “silence” or disparity between their lived experiences and their inherited language of masculinity caused by the new ideologies of parenting. As a response, it is argued that the two protagonists instigate nostalgic backlashes to grapple with the outlets of their crises. While the backlashes materialize as transgressive assertions of “phallic masculinity,”the protagonists eventually become disillusioned with their struggles and opt instead,to come to terms with the crisis of manhood by bonding with certain female characters. This thesis argues that such partial resolutions suggest that both protagonists decide to come to terms with their crises by rearranging “power relations” rather than to assert power as a way toward resolution.